A Preliminary Experimental Investigation of Emotion Dysregulation and Impulsivity in Risky Behaviours. Issue 2 (29th May 2015) - Weiss, Nicole H.; Tull, Matthew T.; Davis, Lindsey T.; Searcy, Jasmin; Williams, Iman; Gratz, Kim L.
<x content-type="archive" xml:space="preserve">Abstract</x> This prospective experimental study sought to examine the unique effects of emotion dysregulation and impulsivity on risky behaviours over time. To this end, 20 African American women enrolled in a historically Black university in the southern United States were randomly assigned to receive one of two brief empirically supported skills training modules (i.e., emotion modulation [EM] or impulsivity reduction [IR]). Participants completed measures of emotion dysregulation, impulsivity, and past-week risky behaviours before (pre-) and one week after (post-) the experimental manipulation. Participants assigned to the EM condition reported significant improvements from pre- to post-manipulation in overall emotion dysregulation (as well as all specific dimensions of emotion dysregulation other than lack of emotional awareness), as well as two dimensions of impulsivity: negative and positive urgency. Participants assigned to the IR condition reported a significant decrease in one dimension of impulsivity (lack of premeditation) from pre- to post-manipulation. Findings also revealed a significant effect of time on risky behaviours, with participants reporting significantly fewer past-week risky behaviours at the post- (vs. pre-) manipulation assessment. Finally, changes in emotion dysregulation from pre- to post-manipulation accounted for the observed reduction in risky behaviours over time (above and beyond changes in impulsivity dimensions). Results highlight the relevance of emotion dysregulation to risky behaviours and suggest that treatments targeting emotion dysregulation may be useful in reducing risky behaviours.